The study on the performance of the gas turbine for power generation - Mohd Aidil, Zaini (2008)
Gas turbines are becoming increasingly used as power generators for a wide variety of applications around the world. Originally they were developed solely for aircraft propulsion where their inherent low specific weight (i.e. mass/unit power) made them essential for high speed flight. For this particular purpose they have been developed to a high degree of efficiency both thermodynamically and mechanically. The significant of this study is to increase the performance of the gas turbine in term of the efficiency. The lower efficiency of the gas turbine will effect to the performance of the gas turbine itself, the waste of the fuel because of the unburned hydrocarbon and the impact to the environment, while the gas turbine with a incomplete combustion. To increase the performance in term of efficiency, the gas generator speed is controlled from 1500 rotary per second to 1250 rotary per second. In order to increase the efficiency of the gas turbine, the power output must high, because it is proportional to the efficiency. Besides low fuel consumption is also important to evaluate an efficient gas turbine because it is inversely proportional to efficiency of the unit. From the experiment, is at a speed of 1400 rotary per second, it is the optimum speed that make the gas turbine running at the highest efficiency. The fuel rate consumption at this speed is 1.48E-03kg/s and the power produce is 905.04W. In conclusion, the optimum speed to run the unit at a high efficiency is at 1400 rotary per second which has produced high power output and low fuel consumption. As a recommendation, to further improve the overall performance of the gas turbine unit, air to fuel ratio must be analyzed, in order to find an optimum air to fuel ratio in the combustion chamber.